FEMINIST DISCOURSE AND AUTOBIOGRAPHICAL WRITING: UNDERCURRENTS OF LOVE, PAIN AND IDENTITY IN THE LITERATURE OF AMRITA PRITAM AND PRABHA KHAITAN - Veena Joshi; Chitlangia, Bhavana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Autobiographies like Amrita Pritam’s ‘Rasidi Ticket’ and Prabha Khaitan’s ‘Anya se Ananya’ not only highlight women’s personal pain, love and identity, but they also define women’s status and consciousness in broader social contexts. In these works, love goes beyond a common human experience. Self-acceptance takes the form of rebellion and self-reliance. The biggest feature of these autobiographies is that here the woman herself is the narrator of her story—neither is she driven by a male gaze nor is she bound by the stereotypical images of society. Amrita’s love is spiritual and silent, while Prabha’s love is analytical and combative—both connect the woman to the depth of her identity. This journey from the ’I’ of the autobiography to the collective ’we’ demonstrates the power of women’s discourse. This research establishes that autobiographical writing, especially in the context of women, is not just memoir writing, but a powerful medium of social and ideological intervention. When a woman searches for her ’self’ in the triangle of love, pain and identity, she provides a new sensibility, new language and new vision to literature. Thus, this research paper not only evaluates the creative contribution of these two writers, but is also an attempt to deeply understand the broad ideological journey of women’s writing in Hindi literature. It is a very beautiful and deep research topic: "Feminist discourse and autobiographical writing: Amrita Pritam and Prabha Khaitan’s